Les compétences pour négocier l’organisation du travail : le cas d’un projet industriel d’automatisation - Agathe Lecoester; Irène Gaillard; Justine Forrierre; Francis Six (Activités)
Our intervention research is based on a project to automate a production sector of a steel company coupled with downsizing. We sought to understand how, within this framework, the working group, made up of supervisors, operators and an ergonomist, managed to design and negotiate an adapted work organization. The analysis of the exchanges within this group shows that the participants’ field knowledge and the knowledge of the ergonomist about the organization of work and the work activity are the basis of the organizational choices that have been made. More specifically, the current and future skills of operators, considered from the point of view of activity and from the point of view of human resources, play a critical role in elaborating an agreement on organizational choices. This finding shows that the point of view of the activity of the operators, associated with an ergonomic methodology helping to integrate it into the design processes, allows organizational choices; these choices take into account the needs of the work activity although the automation choices initially seemed only techno-centered.